Integration of oncologic margins in three-dimensional virtual planning for head and neck surgery, including a validation of the software pathway. Issue 8 (October 2015) - Kraeima, Joep; Schepers, Rutger H.; van Ooijen, Peter M.A.; Steenbakkers, Roel J.H.M.; Roodenburg, Jan L.N.; Witjes, Max J.H.
Abstract: Purpose: Three-dimensional (3D) virtual planning of reconstructive surgery, after resection, is a frequently used method for improving accuracy and predictability. However, when applied to malignant cases, the planning of the oncologic resection margins is difficult due to visualisation of tumours in the current 3D planning. Embedding tumour delineation on a magnetic resonance image, similar to the routinely performed radiotherapeutic contouring of tumours, is expected to provide better margin planning. A new software pathway was developed for embedding tumour delineation on magnetic resonance imaging (MRI) within the 3D virtual surgical planning. Material and methods: The software pathway was validated by the use of five bovine cadavers implanted with phantom tumour objects. MRI and computed tomography (CT) images were fused and the tumour was delineated using radiation oncology software. This data was converted to the 3D virtual planning software by means of a conversion algorithm. Tumour volumes and localization were determined in both software stages for comparison analysis. The approach was applied to three clinical cases. Results: A conversion algorithm was developed to translate the tumour delineation data to the 3D virtual plan environment. The average difference in volume of the tumours was 1.7%. Conclusion: This study reports a validated software pathway, providing multi-modality image fusion for 3D virtual surgical planning.